Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/0276237415594708
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Preference for Polygon Shape

Abstract: shapes can vary in how much they are preferred by observers, but the key factors are still not well understood. In Experiment 1, observers rated the attractiveness of octagonal polygons that varied in contour length but had approximate constant area. Thus, the shapes differed in compactness. Shapes with partial symmetry were judged to be more attractive as were those with greater total contour length. In a second experiment, participants judged polygons with different numbers of concavities but with constant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 20 publications
2
15
0
Order By: Relevance
“…Symmetry affects the perception of complexity. Some scholars have found that, compared with asymmetric shapes with the same number of sides, symmetric shapes have a lower complexity [32]. This may be attributed to the increase in information redundancy caused by the symmetry [23].…”
Section: Symmetry and Complexitymentioning
confidence: 99%
“…Symmetry affects the perception of complexity. Some scholars have found that, compared with asymmetric shapes with the same number of sides, symmetric shapes have a lower complexity [32]. This may be attributed to the increase in information redundancy caused by the symmetry [23].…”
Section: Symmetry and Complexitymentioning
confidence: 99%
“…Observers showed a preference for polygons with greater complexity in contour length and in the number of concavities (Friedenberg & Bertamini, 2015); a correlation between GIF ratio and edge length suggesting a preference for intermediate density over the number of elements in binary chequerboard patterns (Friedenberg & Liby, 2016); and image compression of the contours in nonsense shapes correlated with subjective human judgments for the same shapes whilst avoiding familiarity biases (Forsythe, Mulhern, & Sawey, 2008). Gauvrit et al (2017) reanalysed the data from the study carried out by Friedenberg & Liby (2016) using entropy (in this context, entropy refers to the density of black and white cells in a pattern) and algorithmic complexity (GIF ratio and Block Decomposition Method) and Edge length (the complexity of the edge created by the cells, thus related to the 'crookedness' of the pattern) as additional measures of complexity.…”
Section: Highlightsmentioning
confidence: 99%
“…Already Attneave [ 80 ] found that symmetric shapes are perceived as less complex than asymmetric shapes with the same number of sides. This can probably be attributed to the increase of redundancy caused by symmetry [ 81 , 82 ]. Furthermore, preference of symmetric patterns over scrambled images was explained by the reduction of complexity that goes along with a higher number of symmetry axes [ 83 ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, preference of symmetric patterns over scrambled images was explained by the reduction of complexity that goes along with a higher number of symmetry axes [ 83 ]. Thus, symmetry must be considered as an important aspect of visual complexity [ 40 , 56 , 81 , 84 86 ].…”
Section: Introductionmentioning
confidence: 99%